Desenvolvimento e validação de método multi-resíduos de pesticidas em tomate (Lycopersicum esculentum Mill) in natura por cromatografia líquida de alta frequência (CLAE) - Santos, Viviane Belo dos (2013)
In the last years, the consumption of vegetables and fruits in the world increased, as well as the increase in the use of defensive agricultural to guarantee that production. As a result a growing concern of the citizens and of the scientific community related with the presence and control of residues of pesticides in those products to evaluate the potential risks to the health of the population has occurred. To measure the potential health risk of the population preventive measures are being established so that the undesirable effects are maintained in compatible levels with the life, and also the protection of the cultivated areas. Due to that concern, programs of monitoring of random sampling and the analysis of raw foods and processed at the market are willing to investigate and develop methods which determine this compound in different formers. The objective of this work was to investigate the carbamate occurrence in the acquired samples of tomatoes at the Feira do Produtor, in the State of Roraima, using the technique of the extraction in solid phase for cleaning of the samples and the liquid chromatography of the studied samples. The results indicate that the HPLC/UV-vile procedure resulted in adequate lineal strip, with accuracy, precision and sensibility is adapted for the analysis of residues of pesticides in the tomatoes. The detected limits vary from 1,15 x 10-6 to 9,71 x 10-6 mg L-1 and quantification from 1,15 x 10-6 to 6,23 x 10-5 mg L-1 for all the pesticides studied. The recovery rates obtained for each pesticide ranged from 70 to 100 %, except for the third sample of the pesticide carbofuran (60 %) in which the coefficient of varied less than 20 %. Calibration curves were obtained r2 = 0.999 for nearly all pesticides. The method found that the samples of tomatoes, there were various types of carbamates residues, but most were above the limits established by Brazilian legislation.